Analisis Minat Belajar Matematika Siswa SMP Kelas VIII Pada Materi Persamaan Garis Lurus Berbantu Aplikasi Geogebra - Arpin Chronika Saida Manalu; Yeti Jumiati; Wahyu Setiawan (Journal on Education, 2019)
This research was conducted to analyze the interest in learning of junior high school students when conducting learning aided by the application of geogebra in the material of straight line equatios. The method used in this study is a quasi experiment with percentage quantitative descriptive techniques. The population of this study is students at junior high school Pasundan 9 Bandung, by taking a sample is 33 students of class VIII-C at junior high school Pasundan 9 Bandung. The instrument used in this study was a non-test instrument in the form of a questionnaire about students interest in learning after learning to use a geogebra application consisting of 20 statements. The result of this study are learning straight line equations in whose learning is assisted by the geogebra application get a positive response and can increase student interest in learning. Which can be seen from the average percentage obtained for each indicator 70,74% which means that most students already have an interest in learning mathematics learning mathematics learning assisted by geogebra applications.